2015
DOI: 10.1891/0047-2220.46.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Education and Employment Outcomes from the RSA Data File for Transition-Age African American, White, and Hispanic Youth with Learning Disabilities

Abstract: Relationships among consumer demographic variables, services, and employment outcomes for 25,218 15 to 18 year old youth with learning disabilities were examined using the Rehabilitation Services Administration database from 2012. The 25,218 individuals were randomly split for cross-validation purposes into Sample One and Sample Two. A separate logistic regression was run for each sample. Variables significant for both samples included being African American, college and occupational training, and job placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…Further, the present results suggested that being male, Caucasian, and having a higher level of education were positively associated with competitive employment. This finding is consistent with previous literature regarding people with SLD (Dunham et al 2000;Gonzales et al, 2009;Ji et al, 2015). Researchers repeatedly find that people who come from culturally diverse or otherwise underprivileged backgrounds often feel less empowered and have cultural mistrust (Smart, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, the present results suggested that being male, Caucasian, and having a higher level of education were positively associated with competitive employment. This finding is consistent with previous literature regarding people with SLD (Dunham et al 2000;Gonzales et al, 2009;Ji et al, 2015). Researchers repeatedly find that people who come from culturally diverse or otherwise underprivileged backgrounds often feel less empowered and have cultural mistrust (Smart, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Most notably, job placement, occupational/vocational training, and on-the-job support services had the most robust associations with competitive employment for transition-age youth with SLD. The finding is consistent with other research findings that transition-age youth with SLD need intensive vocational and career preparatory services, all geared toward their individual needs (Ji et al, 2015). Transition-age youth with SLD might need more occupational, vocational, and job skills training from college or universities (Hendricks, 2010) to achieve better employment outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…VR services are most commonly provided by State-run agencies supporting people with disabilities and their vendors, at no cost to people in need of such services (see U.S. Code of Federal Regulations, Assessment for Determining Eligibility & Priority for Services, 2006). Studies show that VR services promote racial disparities, with Black clients less likely to be screened in for services and if screened in less likely to receive job training, less likely to achieve gainful employment, and when employed more likely at lower salaries (Ji et al, 2015). Indeed, research demonstrates that vocational counselors (VCs) generally lack cultural competence in providing services (Vryhof & Balcazar, 2020).…”
mentioning
confidence: 99%
“…Young adults with SMI have low employment rates, with one study showing that only 50% of this population was employed 8 years post-high school, significantlly lower than the 66% rate of employment for young adults generally (Wagner & Newman, 2012). Racial disparities among people with SMI exacerbate these trends; Black young adults with SMI are less likely to find and hold jobs than their White counterparts (Ji et al, 2015; Vryhof & Balcazar, 2020).…”
mentioning
confidence: 99%